Nanoparticle enhanced radiation therapy : principles, methods and applications - Sajo, Erno; Zygmansk, Piotr (IOP series in global health and radiation oncology., 2020)
Improved targeting of abnormal cells and tissue in the radiotherapy of cancer has been a long-standing goal of researchers. The central purpose in Nanoparticle-Enhanced Radiotherapy (NPRT) is to more precisely control where the radiation dose is delivered, desirably with subcellular precision, provided we can find a method to bring the nanoparticles to target and control their concentration and size distribution. The contents within this book will cover the rationale and fundamental principles of NPRT, optimal nanoparticle sizes, concentrations, design and fabrication, effective nanoparticle delivery methods, emerging clinical applications of NRT modalities, treatment planning and quality assurance and the potential of NPRT in global health. This volume will serve as a resource for researchers, educators and industry, and as a practical guide or comprehensive reference for students, research trainees and others working in cancer nanomedicine. Part of IOP Series in Global Health and Radiation Oncology.